Implementasi Design Thinking dalam Inovasi Membangun Model Bisnis Usaha Furniture Hiasan Dinding - Lila Setiyani; Apit Priatna; Anwar Maulana; Evelyn Tjandra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of business business and marketing has become more global, the more developments grow, the emergence of new products from several business competitors so that the level of business competition is increasing. Innovation development must also be owned by a business including Kipong Art, business activities that occur in Kipong Art have the potential to be developed by designing and creating business ideas. This research was conducted to create a business idea that is suitable for Kipong Art's business using the Business Model Canvas (BMC) which is considered easy and simple to understand. While the research steps used are the Design Thinking method and the interview method for data collection conducted to the Kipong Art business owner, so that business ideas can be identified that are suitable for the Kipong Art business business. The results of this study indicate that the business model canvas has a significant impact on the performance of the Kipong Art furniture business. BMC provides a visualization model that makes it easy for business owners to map their business, innovate and create, think simple, collaborate with all the elements needed to run a business, and take advantage of opportunities. The results of this study also show that the strategy using the Business Model Canvas is effective and efficient in determining the business strategy that will be implemented by Kipong Art.